Effect of Organic Practices on Fruit Quality in Papaya Cv. Surya - Y T N Reddy (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
A field experiment was conducted during 2009-10 at Indian Institute of Horticultural Research, Bangalore using papaya cv. 'Surya'. Ten organic nutrient treatments along with recommended dose of fertilizers and control (no manure/fertilizer) were used totaling twelve treatment combinations of FYM, biofertilizers and vermicompost. Fruit quality parameters such as total carotenoids, lycopene, TSS, average fruit weight and ascorbic acid content were analyzed. Among the treatments, application of 50% recommended dose of fertilizers in the form of farm yard manure (FYM) applied as Azospirillum+Phosphate solubilizing bacteria+Mycorrhiza+Vermicompost showed high level of carotenoids, lycopene and low levels of ascorbic acid. TSS and average fruit weight were not affected by various organic nutrient treatments.